Different culture media modulate growth, heterogeneity, and senescence in human mammary epithelial cell cultures. - Jonathan K Lee; Jessica Bloom; Arantzazu Zubeldia-Plazaola; James C Garbe; Martha R Stampfer; Mark A LaBarge (PLoS ONE, 2018)
The ability to culture normal human mammary epithelial cells (HMEC) greatly facilitates experiments that seek to understand both normal mammary cell biology and the many differences between normal and abnormal human mammary epithelia. To maximize in vivo relevance, the primary cell culture conditions should maintain cells in states that resemble in vivo as much as possible. Towards this goal, we compared the properties of HMEC strains from two different reduction mammoplasty tissues that were grown in parallel using different media and culture conditions. Epithelial organoids were initiated into three different media: two commonly used serum-free-media, MCDB 170-type (e.g. MEGM) and WIT-P, and a low stress media, M87A. Growth, lineage heterogeneity, p16 protein expression, and population doublings to senescence were measured for each culture condition. MCDB 170 caused rapid senescence and loss of heterogeneity within 2 to 3 passages, but some cultures went through the 1 to 2 month process of selection to generate clonal finite post-selection post-stasis cells. WIT-P caused impressive expansion of luminal cells in 2nd passage followed by their near complete disappearance by passage 4 and senescence shortly thereafter. M87A supported as much as twice the number of population doublings compared to either serum-free medium, and luminal and myoepithelial cells were present for as many as 8 passages. Thus, of the three media compared, WIT-P and MCDB 170 imposed rapid senescence and loss of lineage heterogeneity, phenotypes consistent with cells maintained in high-stress conditions, while M87A supported cultures that maintained multiple lineages and robust growth for up to 60 population doublings. In conjunction with previous studies examining the molecular properties of cultures grown in these media, we conclude that M87A medium is most able to support long-term culture of multiple lineages similar to in vivo conditions, thereby facilitating investigations of normal HMEC biology relevant to the mammary gland in situ.